Pengaruh Teman Sebaya, Peran Orang Tua, Peran Sekolah, Pengetahuan dan Peran Penyuluhan terhadap Pernikahan Dini - Suciani Suciani; Rindu Rindu; Kusumastuti, Istiana (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Early marriage is a marriage that is carried out at a young age, namely under the age of 18 years. Early marriage can be caused by lack of economy from the family, reproductive health, namely where it is seen from reproductive health such as the uterus where the age of the uterus is not mature enough for fertilization. The purpose of this study was to determine the direct and indirect influence between peers, the role of parents, the role of schools, knowledge, and health counseling on early marriage in the SMPN 1 Kopang area, NTB in 2023. The method used in this study is a quantitative approach using a cross-sectional design. The sample used was 84 female students as respondents. The analysis method used is the Structural Equation Model (SEM) using SmartPLS 3.3 and SPSS 20. The results of hypothesis testing with the Structural Equation Model (SEM) with the smart PLS method found that the variable of early marriage is influenced by peers (31.3%), the role of parents (4.63%), the role of schools (9.64%), knowledge (2.04%), counseling (39.48%). The conclusion obtained in this study is that the role of counseling is a dominant factor that greatly influences early marriage. The more often one receives counseling, the more open one's mindset is in carrying out early marriage. It is expected that the schools in this study will provide more counseling, especially health counseling evenly in each class to add information and knowledge to students who attend school there.